THE GENEALOGY OF TAQNĪN AL-AHKĀM AND ITS INITIAL IMPLEMENTATION IN THE OTTOMAN EMPIRE - Bunyamin, Alby Labib Halbana; Albasyari, Abdul Mufti (JURNAL HAKAM, 2025)
Taqnīn al-Ahkām represents a distinctive mode of applying Islamic jurisprudence (fiqh) within the framework of modern state governance. While the historical emergence of taqnīn has been widely described, its conceptual foundations and theoretical positioning within Islamic legal thought remain insufficiently articulated. This study examines the genealogical development of taqnīn al-Ahkām, tracing its conceptual roots and historical manifestations, and analyzes its role as a juridical strategy for integrating fiqh into formal state legislation. Employing a qualitative historical–conceptual approach based on library research, this study analyzes primary classical texts and relevant secondary sources through contextual and conceptual analysis. The findings demonstrate that ideas resembling taqnīn can be identified as early as the writings of ʿAbd Allāh Ibn al-Muqaffaʿ, although they remained at the level of intellectual proposal. The first systematic and institutionalized implementation of taqnīn occurred during the Ottoman period through the Majalla al-Ahkām al-ʿAdliyyah, which marked a significant transformation of fiqh from normative jurisprudence into a codified legal system. This article argues that taqnīn al-Ahkām should be understood not merely as codification, but as a form of siyāsah sharʿiyyah that mediates between juristic norms and state legal authority. By clarifying the conceptual status of taqnīn within Islamic legal theory, this study contributes to contemporary debates on the adaptability of Islamic law in modern legislative contexts.